Penggunaan Media Sosial Instagram Sebagai Trend Media Dakwah (Studi Kasus Konten Dakwah Akun @jalantaubat) - Muriani, Riska Komala; Faizah, Faizah; Malik, Abdul (Jurnal Ilmiah Global Education, 2024)
Dakwah, which means inviting or calling in Arabic, is an eternal mission to spread Islamic values. Based on Allah's commands in the Koran, da'wah must be carried out with wisdom and in a good manner. In the technological era, social media such as Instagram has become an effective tool for da'wah, especially for the younger generation. The @jalantaubat account is a successful example of using Instagram to spread Islamic messages through interesting and relevant content, making da'wah easier and more effective in achieving happiness and prosperity in this world and the hereafter. This research aims to determine the da'wah messages and social values ​​in the da'wah content of the @jalantaubat Instagram account. The results of this research show that the @jalantaubat account on Instagram spreads da'wah messages about Islamic faith and law, highlighting faith in Allah, angels, messengers, Allah's books, the last day, and Allah's qada and qadar. His message provides a practical understanding of Islamic values ​​for Muslims, including the importance of shaking hands, patience, giving alms, fasting during Ramadan, and providing for the family. The content contains social values ​​such as brotherhood, reminders to use time wisely, appreciating the blessings of health, the importance of apologizing, maintaining harmony, and praying for others are also emphasized.